Long-term, continuous dosing of etanercept in patients with plaque psoriasis. (August 2011) - Papp, Kim A; Krueger, Gerald G; Jemec, Gregor BE; van de Kerkhof, Peter; Robertson, Deborah; Estojak, Joanne; Pedersen, Ronald; Foehl, Joanne; Wajdula, Joseph; Boggs, Robert; Molta, Charles
Psoriasis, a chronic inflammatory skin disease, is characterized by periods of remission and relapse of lesions. Etanercept is approved for treatment of moderate-to-severe plaque psoriasis (25 mg twice weekly or 50 mg weekly). This review of three clinical trials evaluated the efficacy and safety of long-term, continuous (≥≥48 weeks) etanercept therapy in 1887 subjects with moderate-to-severe psoriasis (total exposure: 2458.0 subject-years). Efficacy end points across the three studies included: percent subjects achieving improvement of ≥≥75% from baseline in the Psoriasis Area and Severity Index; mean percentage improvement from baseline of Psoriasis Area and Severity Index; mean Physician''s Global Assessment psoriasis score; and Dermatology Life Quality Index total score (mean percentage improvement from baseline). Safety was also assessed. This article summarizes the sustained efficacy of long-term continuous etanercept therapy, which was generally consistent across the three trials. There were no new or unexpected safety signals with up to 144 weeks of continuous etanercept therapy. Long-term continuous etanercept therapy may be an option for some psoriasis patients.